Vestibular function in the temporal and parietal cortex: distinct velocity and inertial processing pathways - Ventre-Dominey, Jocelyne (Frontiers in Integrative Neuroscience, 2014)
A number of behavioural and neuroimaging studies have reported converging data in favour of a cortical network for vestibular function, distributed between the temporo-parietal cortex and the prefrontal cortex in the primate. In this review, we focus on the role of the cerebral cortex in visuo-vestibular integration including the motion sensitive temporo-occipital areas i.e. the middle superior temporal area (MST) and the parietal cortex. Indeed these two neighbouring cortical regions, though they both receive combined vestibular and visual information, have distinct implications in vestibular function. In sum, this review of the literature leads to the idea of two separate cortical vestibular sub-systems forming (1) a velocity pathway including MST and direct descending pathways on vestibular nuclei. As it receives well defined visual and vestibular velocity signals, this pathway is likely involved in heading perception and rapid top-down regulation of eye/head coordination and (2) an inertial processing pathway involving the parietal cortex in connection with the subcortical vestibular nuclei complex responsible for velocity storage integration. This vestibular cortical pathway would be implicated in high order multimodal integration and cognitive functions, including world space and self- referential processing.